Formula for improving burnability of cement raw material
By using waste slag containing Bi and Te elements in cement raw materials and pre-fired treatment, the problem of high free calcium oxide content after cement raw materials is solved, the stability and burnability of cement are improved, and the needs of industrial production are met.
Patent Information
- Application Number
- CN202510331022.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-20
AI Technical Summary
The free calcium oxide content formed by the existing cement raw materials is high, resulting in insufficient stability and burnability of cement materials. The previous mineralizer solutions are costly and toxic substances are generated, making it difficult to meet industrial production needs.
Waste slag containing Bi and Te elements is used as the component of cement raw materials, and its ability to remove free calcium oxide is improved through pre-firing treatment, temperature and reaction gas are adjusted to desulfurize, and ion replacement is performed with Te and Bi ions and tricalcium silicate, changing its crystal structure, and hindering the densification of the isolation film.
It significantly reduces the residual rate of free calcium oxide in cement clinker, increases the initial and final settling time of cement raw materials, meets the application needs of cement raw materials, and reduces production costs.
Smart Images

Figure CN119822659A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cement manufacturing, and more specifically, to a formula for improving the burnability of cement raw materials. Background Art
[0002] Cement raw material is a material obtained by mixing lime raw materials, clay, iron minerals and a small amount of additives in proportion and grinding them to a certain fineness. Cement raw materials can be calcined to obtain cement clinker. The obtained clinker is one of the main raw materials for cement products and is an indispensable material for wall construction, floor paving and water conservancy projects. The quality of cement raw materials directly affects the service life of cement products.
[0003] During the calcination of cement raw materials, calcium carbonate is mainly decomposed to produce calcium oxide and carbon dioxide. In the high temperature environment of calcination, most of the calcium oxide generated by decomposition will combine with silicon dioxide in limestone or clay components to obtain compound calcium oxide structures, such as C3A (3CaO·Al2O3), C2S (2CaO·SiO2), C3S (3CaO·SiO2), C 12 A7 (12CaO·7Al2O3), these compounded calcium oxides are important components of cement clinker; however, a small amount of calcium oxide is not combined after calcination due to insufficient reaction, thus forming free calcium oxide (f-CaO). These free calcium oxides have extremely strong volume expansion properties when in contact with water. After contacting with water, they can immediately react and produce Ca(OH)2. The instantaneous volume expansion can easily cause stress concentration inside the cement material. The existence of local expansion areas can also cause cement cracking. The existence of free calcium oxide will reduce the stability and burnability of cement raw materials. Therefore, in order to improve the stability and burnability of cement raw materials, it is necessary to reduce the content of free calcium oxide formed after calcination.
[0004] The Chinese patent application document with publication number CN117623671A discloses a cement mineralizer for saving coal and reducing consumption and its preparation method. In the scheme, a mineralizer is obtained by compounding a plurality of organic mixtures with calcium fluoride. The mineralizer can combine with the chemical calcium oxide produced after the cement raw material is burned during the calcination process to obtain a low-melting point solid solution. With the help of the flowable properties of the solid solution, the reaction contact surface of each substance during the calcination process is increased, and finally the residual amount of free calcium oxide in the clinker after calcination is reduced.
[0005] Although the mineralizers in the above documents can increase the reactivity of free calcium oxide by expanding the melt contact surface, the raw materials used in the formula are expensive and cannot meet the actual needs of industrial production. In addition, the decomposition of organic components in the mineralizer will produce toxic substances, and its practical application is relatively limited. Therefore, there is still a demand for designing a resource-friendly cement raw material formula that can significantly reduce the free calcium oxide in cement clinker. Summary of the invention
[0006] In order to further reduce the free calcium oxide content in the clinker after calcining the cement raw meal and further reduce the production cost, the present application provides a formula for improving the burnability of the cement raw meal.
[0007] A formula for improving the burnability of cement raw meal, the formula is prepared by mixing the following raw materials in parts by weight: 80-85 parts of mixed granular material, 8-10 parts of waste slag, and 2-3 parts of iron ore slag; The mixed granular material is obtained by mixing, crushing and sieving limestone and clay; The mass ratio of limestone to clay in the mixed granular material is (5.8-10):1; The preparation of the mixed granules comprises the following steps: Take limestone and clay, mix them, use a Φ420mm×100mm roller press, and the pressure is 4.32-4.37N / mm 2 , roller linear speed 0.41-0.43m / s, process the mixed material for 3-5h, sieve to obtain mixed granules; By adopting the above technical solution, the obtained mixed granular material has the best use effect.
[0008] Preferably, the waste slag is obtained by blending the first mixed material and the second mixed material, pre-burning and crushing, and comprises the following steps: [Ⅰ] taking industrial silicon slag, ball-milling, and sieving to obtain a first mixed material; [II] taking low-grade bismuth sulfide slag, ball-milling, and sieving to obtain a second mixed material; [III] The first mixed material and the second mixed material are mixed, and the obtained mixed material is pre-burned and crushed to obtain the obtained mixed material.
[0009] By adopting the above technical solution, the crushed materials can be fully contacted during mixing, thereby improving the material utilization rate. Among them, pre-burning after the first mixed material and the second mixed material are blended can further reduce the impurity sulfur content and avoid the pollution caused by the large-scale concentrated generation of sulfur dioxide during the raw material calcination process.
[0010] Preferably, the industrial silicon slag includes the following components in mass percentage: SiO2 accounts for 52.5%-55.3%, MgO accounts for 12.1%-15.4%, Al2O3 accounts for 10.9%-12.5%, Fe2O3 accounts for 4.2%-5.1%, and TeS2 accounts for 3.2%-4.7%; the low-grade bismuth sulfur slag includes the following components in mass percentage: SiO2 accounts for 37.2%-40.4%, Ca4Si2O7F2 accounts for 30.5%-32.9%, FeS accounts for 12.6%-15.1%, FeO accounts for 8.7%-10.3%, and Bi2S3 accounts for 3.13%-3.35%.
[0011] By adopting the above technical scheme and using the above industrial silicon slag and low-grade bismuth-sulfur slag as raw materials, the densification process of the tricalcium silicate isolation film formed by the reaction of silicon dioxide and calcium oxide during the subsequent calcination of cement raw materials can be suppressed. During the calcination process, the calcium oxide produced by the decomposition of limestone reacts with the silica microcrystals after the cement raw materials are crushed, and a layer of tricalcium silicate is obtained on the surface of the microcrystals. The tricalcium silicate continues to grow and gradually hardens, and an isolation film will be formed on the surface of the silica microcrystals, and the free calcium oxide will be prevented from continuing to combine with the silica microcrystals. The Te and Bi sulfides used in the scheme exist in the slag in the form of scattered spots. The tellurium oxide and bismuth trioxide obtained by desulfurization after pre-burning are low-melting point components. When the clinker is calcined, the molten ion Te 4+ with Bi 3+ The form of Te exists in the calcined liquid phase. 4+ with Bi 3+ Respectively with Si 4+ With Ca 2+ The ionic radius is similar, and it can diffuse into the tricalcium silicate lattice with the molten liquid phase and partially replace the Si in the tricalcium silicate lattice. 4+ With Ca 2+ , and tricalcium silicate doped with tellurium and bismuth is obtained. Due to the differences in ionic charge and coordination structure at the doping position, lattice defects will be generated in the newly obtained doped tricalcium silicate crystals, which will affect the densification process of the isolation film, making the tricalcium silicate isolation film more easily disintegrated under the heat and mechanical movement of hot air in the furnace. The exposed active silica reaction sites can further combine with free calcium oxide, ultimately reducing the residual content of free calcium oxide in the clinker product.
[0012] Preferably, the particle size of the first mixture is 0.5-1 mm, and the particle size of the second mixture is 2-3 mm; the first mixture and the second mixture are mixed in a mass ratio of (1-1.5):1.
[0013] By adopting the above technical solution, using the first mixture and the second mixture with the particle size and mixing ratio, the pre-burning effect after mixing is optimal. Through the crushing process, the TeS2 and Bi2S3 microcrystalline structures in the slag can be exposed to a greater extent, thereby enhancing the subsequent pre-burning desulfurization effect.
[0014] Preferably, the pre-burning operation parameters are: controlling the temperature of the reactor to 500-650°C, then introducing the reaction gas, keeping the temperature constant for 1-2 hours, and then gradually reducing the temperature; The gradient cooling is to reduce the material temperature to 50-55°C at a cooling rate of 5.3-7.5°C / min, and then let it stand at room temperature overnight.
[0015] By adopting the above technical scheme, regulating the pre-burning temperature and the reaction gas composition, the sulfur element in industrial silicon slag and low-grade bismuth-sulfur slag can be effectively removed. The use of gradient cooling helps to improve the quality of raw materials and enhance their chemical efficiency with free calcium oxide during the subsequent calcination of cement raw materials.
[0016] Preferably, the reaction gas is obtained by mixing oxygen and nitrogen in a volume ratio of (2.5-3):1.
[0017] By adopting the above technical scheme, the oxygen in the reaction gas can react with the various sulfur-containing compounds in the first mixture and the second mixture, convert the metal sulfides in the slag into metal oxides, convert the fixed sulfur element into sulfur dioxide through oxidation reaction, and remove the material-slag system. The bismuth trioxide and tellurium oxide produced after the reaction are low-melting point components. During the clinker calcination stage, they are distributed in the calcination liquid phase in the form of molten ions, diffuse with the liquid phase to the lattice boundary of tricalcium silicate, and molten ion replacement occurs.
[0018] In summary, this application has the following beneficial effects: 1. This application uses waste slag containing Bi and Te elements as a component of cement raw material. In the subsequent cement raw material calcination stage, Bi and Te element ions diffuse with the cement raw material molten liquid phase to the edge of tricalcium silicate crystals on the surface of silicon dioxide microcrystals, and replace Si in tricalcium silicate. 4+ , Ca 2+ The lattice position is changed to obtain tricalcium silicate doped with Te and Bi. Due to the influence of the doped ions, the tricalcium silicate lattice produces defects and distortions, which hinders the process of densification of tricalcium silicate and formation of an isolation film, and reduces the difficulty of the free calcium oxide combining with the silicon dioxide inside the isolation film.
[0019] 2. In the present application, the first mixed material and the second mixed material are preferably pre-burned to obtain waste slag to improve its ability to remove free calcium oxide in the clinker. By adjusting the temperature and the reaction gas, desulfurization can be effectively achieved. After desulfurization, the Bi and Te elements in the waste slag exist in the form of low-melting oxidation states, which can be melted with the raw material molten liquid phase in the subsequent raw material calcination process, and undergo ion replacement with tricalcium silicate in the form of molten ions, thereby changing the stability of the crystal structure of tricalcium silicate.
[0020] 3. By adopting the cement raw material formula of the present application, the residual rate of free calcium oxide in the clinker obtained after calcination is less than 0.35%, the initial setting time of the obtained cement is greater than 5.3h, and the final setting time is greater than 8.4h, which meets the application requirements of cement raw material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the XRD diagram of the clinker powder product after thermal combustion of cement raw materials in Example 2 of the present application.
[0022] Figure 2 It is the content of free calcium oxide in the clinker after hot burning of cement raw materials in Examples 1-3 of the present application and Comparative Examples 1-2.
[0023] Figure 3 The initial setting time and final setting time of cement products made from cement raw materials of Examples 1-3 and Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION
[0024] Example 1 The formulation of this embodiment is prepared by mixing the following raw materials in parts by weight: 800 g of mixed granular material, 80 g of waste slag, and 20 g of iron ore slag.
[0025] The preparation steps of the mixed pellets in this embodiment are as follows: Take 1160g limestone and 200g clay, mix them in a mixer, adjust the speed to 50rpm, process for 0.5h, then use a Φ420mm×100mm roller press, adjust the pressure to 4.32N / mm 2 , roller linear speed 0.41m / s, process the mixed material for 3h, and sieve out the mixed particles with an average particle size of 20mm for use.
[0026] The steps for preparing the waste slag in this embodiment are as follows: [I] Take 950g of industrial silicon slag, control the ball-to-material ratio to 3:1, ball mill speed to 125rpm, process for 35min, then sieve and take the slag with an average particle size of 0.5mm as the first mixed material; [II] Take 800g of low-grade bismuth sulfide slag, control the ball-to-material ratio to 3:1, ball mill speed to 85rpm, process for 30min, then sieve and take the slag with an average particle size of 2mm as the second mixed material.
[0027] [III] Take 500g of the first mixed material and 500g of the second mixed material, use a mixer to mix, adjust the speed to 80rpm, and process for 0.5h to obtain a mixed material. Then place the mixed material in a reactor, raise the temperature in the reactor to 500℃, introduce the reaction gas into the reactor at a flow rate of 0.2L / min, and react at a constant temperature for 1h, then reduce the temperature of the reactor to 50℃ at a rate of 5.3℃ / min, let it stand at room temperature overnight, and then use a Φ420mm×100mm roller press to crush it, and adjust the pressure to 5.25N / mm 2 , roller linear speed 0.63m / s, process the mixed material for 2h, and the product is obtained.
[0028] Among them, the raw material composition of limestone is: CaO accounts for 47.93%, SiO2 accounts for 0.67%, Al2O3 accounts for 1.37%, Fe2O3 accounts for 0.32%, TiO2 accounts for 1.96%, SO3 accounts for 0.03%, MgO accounts for 0.12%, others account for 1.69%, and ignition loss accounts for 45.91%. The raw material composition of clay is: SiO2 accounts for 53.5%, K2O accounts for 4.2%, MgO accounts for 2.1%, Fe2O3 accounts for 6.7%, Al2O3 accounts for 20.3%, and others account for 13.2%. The raw material composition of industrial silicon slag is: SiO2 accounts for 52.5%, MgO accounts for 12.1%, Al2O3 accounts for 10.9%, Fe2O3 accounts for 4.2%, and TeS2 accounts for 3.2%. The raw material composition of low-grade bismuth sulphide slag is: SiO2 accounts for 37.2%, Ca4Si2O7F2 accounts for 30.5%, FeS accounts for 12.6%, FeO accounts for 8.7%, and Bi2S3 accounts for 3.13%. The average particle size of iron ore slag is 12mm, and the raw material composition is: SiO2 accounts for 17.24%, Fe2O3 accounts for 21.47%, Al2O3 accounts for 4.98%, CaO accounts for 40.29%, and the loss on ignition accounts for 16.02%. The reaction gas is obtained by mixing oxygen and nitrogen in a volume ratio of 2.5:1.
[0029] Example 2 The formulation of this embodiment is prepared by mixing the following raw materials in parts by weight: 825 g of mixed granular material, 85 g of waste slag, and 25 g of iron ore slag.
[0030] The preparation steps of the mixed pellets in this embodiment are as follows: Take 1180g limestone and 200g clay, mix them in a mixer, adjust the speed to 60rpm, process for 0.5h, then use a Φ420mm×100mm roller press, adjust the pressure to 4.35N / mm 2 , roller linear speed 0.42m / s, process the mixed material for 3h, and sieve out the mixed granular material with an average particle size of 25mm for use.
[0031] The steps for preparing the waste slag in this embodiment are as follows: [I] Take 950g of industrial silicon slag, control the ball-to-material ratio to 4:1, ball mill speed to 135rpm, process for 40min, then sieve and take the slag with an average particle size of 1mm as the first mixed material; [II] Take 835g of low-grade bismuth sulfide slag, control the ball-to-material ratio to 4:1, ball mill speed to 90rpm, process for 35min, then sieve and take the slag with an average particle size of 3mm as the second mixed material.
[0032] [III] 650g of the first mixed material and 500g of the second mixed material were mixed using a mixer at a speed of 85rpm for 1h to obtain a mixed material. The mixed material was then placed in a reactor, the temperature in the reactor was raised to 600°C, and the reaction gas was introduced into the reactor at a flow rate of 0.3L / min. The reaction was carried out at a constant temperature for 2h, and then the temperature of the reactor was reduced to 55°C at a rate of 6.5°C / min. After standing at room temperature overnight, it was crushed using a Φ420mm×100mm roller press and the pressure was adjusted to 5.25N / mm 2 , roller linear speed 0.67m / s, process the mixed material for 2.5h, and the product is obtained.
[0033] Among them, the raw material composition of limestone is: CaO accounts for 47.93%, SiO2 accounts for 0.67%, Al2O3 accounts for 1.37%, Fe2O3 accounts for 0.32%, TiO2 accounts for 1.96%, SO3 accounts for 0.03%, MgO accounts for 0.12%, others account for 1.69%, and ignition loss accounts for 45.91%. The raw material composition of clay is: SiO2 accounts for 53.5%, K2O accounts for 4.2%, MgO accounts for 2.1%, Fe2O3 accounts for 6.7%, Al2O3 accounts for 20.3%, and others account for 13.2%. The raw material composition of industrial silicon slag is: SiO2 accounts for 55.3%, MgO accounts for 14.2%, Al2O3 accounts for 12.5%, Fe2O3 accounts for 4.4%, and TeS2 accounts for 4.7%. The raw material composition of low-grade bismuth sulphide slag is: SiO2 accounts for 40.4%, Ca4Si2O7F2 accounts for 31.5%, FeS accounts for 14.2%, FeO accounts for 9.7%, and Bi2S3 accounts for 3.35%. The average particle size of iron ore slag is 12mm, and the raw material composition is: SiO2 accounts for 17.24%, Fe2O3 accounts for 21.47%, Al2O3 accounts for 4.98%, CaO accounts for 40.29%, and the loss on ignition accounts for 16.02%. The reaction gas is obtained by mixing oxygen and nitrogen in a volume ratio of 3:1.
[0034] Example 3 The formulation of this embodiment is prepared by mixing the following raw materials in parts by weight: 850 g of mixed granular material, 100 g of waste slag, and 30 g of iron ore slag.
[0035] The preparation steps of the mixed pellets in this embodiment are as follows: Take 2000g limestone and 200g clay, use a mixer to mix, adjust the speed to 60rpm, process for 1h, then use a Φ420mm×100mm roller press, adjust the pressure to 4.37N / mm 2 , roller linear speed 0.43m / s, process the mixed material for 5h, and sieve out the mixed particles with an average particle size of 30mm for use.
[0036] The steps for preparing the waste slag in this embodiment are as follows: [I] Take 1000g of industrial silicon slag, control the ball-to-material ratio to 5:1, ball mill speed to 137rpm, process for 45min, then sieve and take the slag with an average particle size of 1mm as the first mixed material; [II] Take 850g of low-grade bismuth sulfide slag, control the ball-to-material ratio to 4:1, ball mill speed to 90rpm, process for 40min, then sieve and take the slag with an average particle size of 3mm as the second mixed material.
[0037] [III] 750g of the first mixed material and 500g of the second mixed material were mixed using a mixer at a speed of 90rpm for 1h to obtain a mixed material. The mixed material was then placed in a reactor, the temperature in the reactor was raised to 650°C, and the reaction gas was introduced into the reactor at a flow rate of 0.35L / min. The reaction was carried out at a constant temperature for 2h, and then the temperature of the reactor was reduced to 55°C at a rate of 7.5°C / min. After standing at room temperature overnight, it was crushed using a Φ420mm×100mm roller press and the pressure was adjusted to 5.32N / mm 2 , roller linear speed 0.71m / s, process the mixed material for 2h, and you will get it.
[0038] Among them, the raw material composition of limestone is: CaO accounts for 47.93%, SiO2 accounts for 0.67%, Al2O3 accounts for 1.37%, Fe2O3 accounts for 0.32%, TiO2 accounts for 1.96%, SO3 accounts for 0.03%, MgO accounts for 0.12%, others account for 1.69%, and ignition loss accounts for 45.91%. The raw material composition of clay is: SiO2 accounts for 53.5%, K2O accounts for 4.2%, MgO accounts for 2.1%, Fe2O3 accounts for 6.7%, Al2O3 accounts for 20.3%, and others account for 13.2%. The raw material composition of industrial silicon slag is: SiO2 accounts for 54.7%, MgO accounts for 15.4%, Al2O3 accounts for 11.9%, Fe2O3 accounts for 5.1%, and TeS2 accounts for 3.21%. The raw material composition of low-grade bismuth sulphide slag is: SiO2 accounts for 38.4%, Ca4Si2O7F2 accounts for 32.9%, FeS accounts for 15.1%, FeO accounts for 10.3%, and Bi2S3 accounts for 3.27%. The average particle size of iron ore slag is 12mm, and the raw material composition is: SiO2 accounts for 17.24%, Fe2O3 accounts for 21.47%, Al2O3 accounts for 4.98%, CaO accounts for 40.29%, and the loss on ignition accounts for 16.02%. The reaction gas is obtained by mixing oxygen and nitrogen in a volume ratio of 3:1.
[0039] Comparative Example 1 The difference between this comparative example and Example 1 is that the formula is prepared by mixing the following raw materials in parts by weight: 800 g of mixed granular material, 80 g of coal gangue, and 20 g of iron ore slag.
[0040] Among them, the chemical composition of coal gangue (average particle size is 35mm) is: SiO2 accounts for 47.3%, Al2O3 accounts for 31.6%, Fe2O3 accounts for 10.3%, CaO accounts for 2.5%, MgO accounts for 1.7%, and the remaining components account for 6.6%.
[0041] The remaining steps are the same as those in Example 1.
[0042] Comparative Example 2 The difference between this comparative example and Example 1 is that the formula is prepared by mixing the following raw materials in parts by weight: 800 g of mixed granular material, 80 g of the first mixed material, and 20 g of iron ore slag.
[0043] In this comparative example, the preparation steps of the first mixed material are: [i] 950 g of industrial silicon slag was taken, the ball-to-material ratio was controlled to 3:1, the ball milling speed was 125 rpm, the treatment was carried out for 35 min, and then the slag with a particle size of 0.5 mm was sieved and taken as the first mixed material; [ii] The first mixed material is added into a reaction kettle, the temperature in the kettle is raised to 500°C, and then the reaction gas is introduced into the kettle at a flow rate of 0.2L / min. The reaction is carried out at a constant temperature for 1 hour, and then the temperature of the kettle is reduced to 50°C at a rate of 5.3°C / min. The mixture is allowed to stand at room temperature overnight to obtain the product.
[0044] The reaction gas is obtained by mixing oxygen and nitrogen in a volume ratio of 2.5:1.
[0045] The remaining steps are the same as those in Example 1.
[0046] Performance testing Cement clinker powder XRD test The formula of Example 2 was placed in a high temperature furnace, preheated at 800°C, and then calcined at 1400°C for 2h. The calcined product was then sieved through an 800-mesh sieve and a powder sample of the product was taken for XRD testing. The test results are as follows: Figure 1 shown.
[0047] Free calcium oxide content detection In the national standard GB / T26566-2011, the burnability of cement is explained as the difficulty of forming cement clinker through calcination of cement raw materials. That is, the burnability can be indicated by testing the content of residual free calcium oxide in the clinker after the cement raw materials are calcined into cement clinker.
[0048] Referring to the national standard GB / T26566-2011 "Test method for calcinability of cement raw materials" and the national standard GB / T176-2017 "Cement chemical analysis method", 100 g of samples of Examples 1-3 and Comparative Examples 1-2 were taken, 10 mL of distilled water was added respectively and stirred into a mass, 3.6 g of each group of water-containing samples were taken, and a mold was used under a working pressure of 10.6 kN to press into a Φ13 mm specimen, and then placed in a 105 ° C oven for drying, and then the dried product was placed in a 950 ° C constant temperature pre-burning high-temperature furnace for treatment for 30 min, and naturally cooled for standby use.
[0049] Weigh about 0.5g of sample (m) to an accuracy of 0.0001g, place it in a 250mL dry conical flask, add 10mL of anhydrous ethanol and 20mL of ethylene glycol, put in a dry stirring bar, install a condenser, place it on a free calcium oxide tester (model: Ca-5A), adjust the magnetic stirring speed to 50rpm, and heat it to boil at the same time. When the ethanol in the condensed state begins to drip continuously, continue to heat to a slight boil for 5min under stirring, then remove the conical flask, and use a glass sand core funnel equipped with a vacuum pump to filter the sample solution while hot into a 250mL suction flask, and then wash the conical flask and precipitate with anhydrous ethanol for 3 times. Add 50mL of water and 5mL of 18.5% hydrochloric acid into the filtration bottle, shake well, add 5mL of 33.3% triethanolamine solution and an appropriate amount of CMP mixed indicator, add 200g / L potassium hydroxide solution while shaking until green fluorescence appears, then add 5-8mL in excess, and record the added volume (V) when the green fluorescence disappears completely and turns red with EDTA standard titration solution.
[0050] Free calcium oxide W fCaO The calculation formula is:
[0051] W fCaO : Mass fraction of calcium oxide, %; T CaO : The titration degree of EDTA standard titration solution on calcium oxide, in milligrams per milliliter (mg / mL); V: The volume of EDTA standard titration solution consumed during titration, in milliliters (mL); m: The mass of the sample, in grams (g).
[0052] Cement clinker initial and final setting time test With reference to the national standard GB / T1346-2011 "Test Method for Water Consumption, Setting Time and Stability of Cement Standard Consistency", take 500g of samples of Examples 1-3 and Comparative Examples 1-2, cook and cool them, add 5% gypsum by mass, add water and stir to obtain a standard consistency slurry, add water and place it for a test needle sinking test, when the test needle sinks to 4mm±1mm from the bottom plate, the cement reaches the initial setting state. The time from the cement being fully added to the water to the initial setting state is the initial setting time of the cement, expressed in min; when the test needle accessories begin to leave no trace on the specimen, the cement reaches the final setting state. The time from the cement being fully added to the water to the final setting state is the final setting time of the cement, expressed in min.
[0053] Analyze Example 2 and Comparative Examples 1-2 and combine Figure 1 and Figure 2It can be seen that after the cement raw material is thermally burned, in addition to the calcium silicate crystals (C2S and C3S) formed by Ca and SiO2, there are also several new crystal structures containing Te and Bi ions in the obtained cement clinker powder, indicating that Bi and Te ions have achieved effective doping effect in calcium silicate crystals; and from the diffraction peak results, there are C2S, C3S, Ca3Bi2(Te2Si)2O at the position of 2θ=21.4°. 15 and the mixed peak of Ca2Bi2SiO7, indicating that part of C2S and C3S have been transformed into doped crystal structures containing Te and Bi; combined with Figure 2 From the residual content of free calcium oxide in Example 2 and Comparative Examples 1-2, it can be concluded that the introduction of Te and Bi ions in Example 2 improves the utilization rate of free calcium oxide. This indicates that the presence of the newly formed doped crystals makes the combination of free calcium oxide and SiO2 higher. The reason for this phenomenon may be that the presence of the doped crystal structure inhibits the densification process of calcium silicate crystals, and the free calcium oxide generated during the calcination process is more likely to pass through the isolation membrane composed of C2S and C3S and react with the inner layer of silicon dioxide wrapped by the isolation membrane.
[0054] Analyze Examples 1-3 and Comparative Example 1 and combine Figure 2 and Figure 3 It can be seen that after using coal gangue as the raw material component of cement raw material in Comparative Example 1, the content of free calcium oxide after calcining the cement raw material suddenly increased and the initial and final setting time of the cement product was shortened. This may be because there is a certain amount of carbon-containing organic matter in the composition of coal gangue, and this part of organic matter has a high calorific value. During the calcination of raw materials, the organic matter decomposes and releases a large amount of heat, which leads to overburning of the raw materials, and the reaction of silicon dioxide in the raw materials with free calcium oxide is hindered, thereby causing an increase in free calcium oxide in the clinker product; and with the accumulation of free calcium oxide in the clinker, the hydration activity of the cement clinker increases, and ultimately shortens the initial and final setting time of the cement, and reduces the stability of the cement.
[0055] Analyze Examples 1-3 and combine Figure 2 and Figure 3 It can be seen that among the three embodiments, the cement raw material produced by the raw materials and proportions used in Example 2 has the best effect.
[0056] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A formula for improving the burnability of cement raw meal, characterized in that: The formula is prepared by mixing the following raw materials in parts by weight: 80-85 parts of mixed granular material, 8-10 parts of waste slag, and 2-3 parts of iron ore slag; the average particle size of the iron ore slag is 12 mm; The mixed granular material is obtained by mixing, crushing and sieving limestone and clay.
2. A formulation for improving the burnability of cement raw meal according to claim 1, characterized in that: The mass ratio of limestone to clay in the mixed granular material is (5.8-10):
1.
3. A formulation for improving the burnability of cement raw meal according to claim 1, characterized in that: The preparation of the mixed granules comprises the following steps: Take limestone and clay, mix them, use a Φ420mm×100mm roller press, and the pressure is 4.32-4.37N / mm 2 , roller linear speed 0.41-0.43m / s, process the mixed material for 3-5h, sieve to obtain mixed granules.
4. A formulation for improving the burnability of cement raw meal according to claim 1, characterized in that: The waste slag is obtained by mixing the first mixed material and the second mixed material, pre-burning and crushing, and comprises the following steps: [I] taking industrial silicon slag, ball-milling, and sieving to obtain a first mixed material; [II] taking low-grade bismuth sulfide slag, ball-milling, and sieving to obtain a second mixed material; [III] The first mixed material and the second mixed material are mixed, and the obtained mixed material is pre-burned and crushed to obtain the obtained mixed material.
5. A formula for improving the burnability of cement raw meal according to claim 4, characterized in that: The industrial silicon slag includes the following components in mass percentage: SiO2 accounts for 52.5%-55.3%, MgO accounts for 12.1%-15.4%, Al2O3 accounts for 10.9%-12.5%, Fe2O3 accounts for 4.2%-5.1%, and TeS2 accounts for 3.2%-4.7%.
6. A formulation for improving the burnability of cement raw meal according to claim 4, characterized in that: The low-grade bismuth sulphide slag includes the following components in mass percentage: SiO2 accounts for 37.2%-40.4%, Ca4Si2O7F2 accounts for 30.5%-32.9%, FeS accounts for 12.6%-15.1%, FeO accounts for 8.7%-10.3%, and Bi2S3 accounts for 3.13%-3.35%.
7. A formula for improving the burnability of cement raw meal according to claim 4, characterized in that: The particle size of the first mixed material is 0.5-1 mm, and the particle size of the second mixed material is 2-3 mm; the first mixed material and the second mixed material are mixed in a mass ratio of (1-1.5):
1.
8. A formula for improving the burnability of cement raw meal according to claim 4, characterized in that: The pre-burning operation parameters are: controlling the temperature of the reactor to 500-650° C., then introducing the reaction gas, maintaining the temperature for 1-2 hours, and then gradually reducing the temperature.
9. A formulation for improving the burnability of cement raw meal according to claim 8, characterized in that: The reaction gas is obtained by mixing oxygen and nitrogen in a volume ratio of (2.5-3):
1.
10. A formula for improving the burnability of cement raw meal according to claim 8, characterized in that: The gradient cooling is to reduce the material temperature to 50-55°C at a cooling rate of 5.3-7.5°C / min, and then let it stand at room temperature overnight.
Citation Information
Patent Citations
Coal-saving and consumption-reducing cement mineralizer and preparation method thereof
CN117623671A
Method for preparing low energy consumption cement with tin ore tailings as raw materials for resource utilization
CN103524059A
Green and environment-friendly cement and preparation method thereof
CN111268929A
Method and plant for treating raw-meal in a cement clinker manufacturing process
WO2023165977A1